Conveying Environmental Information to Deafblind People: A Study of Tactile Sign Language Interpreting - Gabarró-López, Sílvia; Mesch, Johanna (Frontiers in Education, 2020)
Many deafblind people use tactile sign language and interpreters in their daily lives. Because of their hearing and sight loss, the role of interpreters does not only involve translating the content expressed by other deaf or hearing people, but it also involves conveying environmental information (i.e., non-verbal communication regarding what is happening at a given moment to be able to understand the situation). This paper aims to contribute to the field of tactile sign language interpreting by describing how two tactile Swedish Sign Language interpreters convey environmental information to two deafblind women in a particular situation, that is, a guided visit to a cathedral with a hearing Norwegian speaker. We expect to find different strategies including the use of haptic signs (i.e., a system of signs articulated in the body of the deafblind person aimed to provide environmental and interactional information). After summarizing the small amount of existing research on the issue to date, we present our data and how they were annotated. Our analysis shows that a variety of strategies are used including using tactile Swedish Sign Language, using locative points to show locations with some type of contact with the body of deafblind individuals, depicting shapes on the palm of the hand of deafblind individuals, using objects to depict shapes, touching elements of the setting with the hands or with the feet such as surfaces, and walking around the place. Some of them are more frequent than others and some strategies are also used in combination, whereas others are used in isolation. We did not observe any use of haptic signs to convey environmental information in our data, which calls for further research on which criteria apply to use this strategy in a particular situation.